Addressing scabies among street children in Ethiopia: an ethnographic study of acceptable interventions by prospective recipients and deliverers - Zewude, Bewunetu; Ayode, Desta; Davey, Gail; Zaman, Shahaduz; Tadele, Getnet (Frontiers in Public Health, 2025)
IntroductionScabies is a neglected tropical disease that affects the physical, socioeconomic, and psychological wellbeing of patients. Street children, due to poor living conditions and social marginalization, are at increased risk of infestation and face significant barriers to access healthcare services. Various interventions to control scabies have been suggested and implemented, but few have been based on the needs and viewpoints of the street children themselves. Drawing on the theoretical framework of acceptability (TFA), this article explores the interventions that street children, parents, and other key informants perceived to be appropriate to control scabies among street children.MethodsAn ethnographic approach was adopted to collect qualitative data from purposively selected street children, parents/caregivers, and key informants representing NGOs and the health and social sectors in Addis Ababa, Hawassa, and Adama. Rich data were gathered using FGDs, in-depth interviews, key informant interviews and drawing exercises, enhancing children's engagement in the study. Interviews were conducted in participants' preferred languages, recorded, transcribed verbatim, and translated into English for analysis. Data were coded by the two researchers who had collected them, and themes and sub-themes were identified.ResultsLiving in overcrowded conditions, lack of access to sanitation materials and health services were among the priority needs and lived experiences of the street children. Providing peer-led health education, educating and mobilizing existing healthcare providers, preventing child streetism, raising the awareness of the community children migrate from, and providing sanitation facilities were among the proposed interventions that were considered appropriate to control scabies among street children.ConclusionCollaborative and participatory interventions that align with the lived experiences of street children and other stakeholders are likely to increase participation and enhance the feasibility and impact of scabies control and elimination efforts.